The specialized educational and psychological counseling in inflammatory bowel disease patients – a target or a challenge? - Gavrilescu, Otilia; Prelipcean, Cristina Cijevschi; Dranga, Mihaela; Soponaru, Camelia; Mihai, Catalina (Turkish Journal of Gastroenterology, 2020)
Background/Aims: Stress, in its various forms, plays an important role in the development and evolution of inflammatory bowel disease (IBD). For patients with IBD, the evidence related to the effects of various types of psychological therapies remains inconclusive. This study aimed to evaluate whether cognitive behavioral therapy, in combination with educational counseling, influenced disease activity and quality of life (QoL) among patients with IBD. Materials and Methods: We conducted a randomized controlled trial with 60 patients diagnosed with IBD. All patients completed the IBD questionnaire-32 (IBDQ-32) and the Big Five Inventory. Group A (experimental group) received specialized educational and psychological counseling (SEPC), and group B (control group) was treated according to the current medical practice. All patients were reassessed after 12 months. Results: After the SEPC, there was no improvement in disease activity as estimated by fecal calprotectin levels. However, the QoL of patients in group A was significantly improved. The highest mean difference between the initial and final IBDQ scores was found among patients whose main personality trait was openness to experience (48.58±28.80), and the lowest mean difference between these 2 scores was found among patients whose main personality trait was closedness to experience (3.33±2.97, p=0.009). Conclusion: Although there was no improvement in disease activity after the SEPC, this therapy improved patients’ QoL in terms of both emotional and social functions, especially among patients whose dominant personality trait was openness to experience or neuroticism.